If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65X + 30Y = 45(X + Y) 65X + 30Y = (X * 45 + Y * 45) 65X + 30Y = (45X + 45Y) Solving 65X + 30Y = 45X + 45Y Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-45X' to each side of the equation. 65X + -45X + 30Y = 45X + -45X + 45Y Combine like terms: 65X + -45X = 20X 20X + 30Y = 45X + -45X + 45Y Combine like terms: 45X + -45X = 0 20X + 30Y = 0 + 45Y 20X + 30Y = 45Y Add '-30Y' to each side of the equation. 20X + 30Y + -30Y = 45Y + -30Y Combine like terms: 30Y + -30Y = 0 20X + 0 = 45Y + -30Y 20X = 45Y + -30Y Combine like terms: 45Y + -30Y = 15Y 20X = 15Y Divide each side by '20'. X = 0.75Y Simplifying X = 0.75Y
| 2n^3+3n^2-8n-12=0 | | -46=-3x+14 | | -5+5x-3x=-1 | | -89=7x+4x+10 | | 8x^2+7x=36x-9 | | -(7y+4)-(-6y-5)=-5 | | 5.6e=3.2 | | -9-x-7x=-41 | | 4-3p+7+4p= | | 5x^2-15x-35= | | 5h=6.5 | | (5x^2-4x-1)-(-4x^2-4)= | | -4-3x+4x=-1 | | 33x=-7 | | 2x^2+x+7=0 | | 33x=35 | | x+5x-4=18-2 | | 4x-6(.74)=-2 | | 5+2m-1=7m+11-4m | | 5/11=-3b/11+8b/22 | | 7(6y-2/4)-5y=24 | | -4-x+3x=-26 | | y=(x-4)(x+9) | | 10+2x=-12 | | 44=5-6 | | 7x-4y=84 | | (5x-4)=3x*2 | | 8x=4+2y | | 12(x-2)=1-x | | (a-4)(a-4)=0 | | 5x-4=(3x*2) | | (t-5)(t-5)=0 |